(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study examined the phenomenon of unemployment in Iraq and the extent of the contribution of these loans granted by banks to finance small and medium enterprises in reducing their rates. The temporal boundaries of the study included the period between (2012-2018). The spatial boundaries consisted of random sampling of six Iraqi banks) Where the government banks included (Rafidain, Rasheed and industrial), private banks included (the Iraqi Islamic Bank and the Gulf Commercial Bank and the Bank of the Middle East). In order to achieve the objective of the research in the light of the hypotheses drawn up, the research divided into three topics, the first section highlighting the reality of small and medium enterprises in Iraq and the loans granted to them within several programs. The second part of this research included the study of the most important related to small and medium enterprises in terms of their concept, types and characteristics, knowledge of the importance and challenges faced by them and the reality of the loans granted to them. Finally, the third topic has been addressed, and before reviewing the results and analysis, Through a review of a sample of government and private banks to be then move to the presentation of the results of the field and analysis after the processing of statistical analysis and the results by diagnosing the reality of the variables of the study into two main variables: But the research sample banks to finance small and medium enterprises, to reduce unemployment, which is the second variable in this study. Finally, test the hypothesis of research. The main conclusions of the researcher are that supporting small and medium-sized enterprises through the granting of loans contributes to the growth and improvement of these projects in the framework of private sector development. Funding also contributes to the success and continuation of these projects to reduce unemployment. Unemployed or job seekers to obtain a job opportunity that suits their qualifications, qualifications and qualifications in all respects, rather than relying on the public service provided by the state. Therefore, it recommended adopting ways to promote small and medium-sized enterprises with the contents of policies and programs sector and college through the pursuit of integration of small and medium enterprises activities with commercial activities, industrial and agricultural integration considered the most important reasons for the success of these projects.